Question the promise: validating the interprofessional attitudes scale in Vietnamese health students. - Tran, Linh Thuy Khanh; Duong, Khoa Duy; Le, Duong Dai; Nguyen, Hoang Thi Mai (Journal of Interprofessional Care)
The Interprofessional Attitudes Scale (IPAS) is a promising tool for assessing interprofessional education (IPE) attitudes, especially in community-oriented initiatives. To meet the need for validated IPE tools in Vietnam, we translated the IPAS into Vietnamese (Viet-IPAS) and evaluated its psychometric properties. The preparatory phases included forward and backward translation, expert consultations, and student feedback, resulting in strong content validity, face validity, linguistic comprehensibility, and test-retest reliability. During the 2020–2021 academic year, health students from the University of Medicine and Pharmacy at Ho Chi Minh City were invited for the main phase. A total of 282 students from medical, nursing, pharmacy, and rehabilitation science programs completed an online survey using the Viet-IPAS. Cronbach's alphas for the Teamwork, roles and responsibilities (TRR), Patient-centeredness, Interprofessional biases (IB), Diversity and ethics, and Community-centeredness subscales were.84,.79,.56,.86, and.81, respectively. Confirmatory factor analysis indicated an acceptable fit (normed χ2: 2.618, RMSEA:.076, CFI:.874, AGFI:.77). Factor loadings were above.70, except for IB3 and TRR8 items. Modified models by removing IB subscale and TRR8 item showed slightly improved fit. We recommend using the Viet-IPAS with modifications in Vietnamese health student populations and encourage further review and refinement of the instrument.